THE EFFECTS OF BOARD DIVERSITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: CASE STUDY OF MAIN SECTOR COMPANY LISTED IN IDX PERIOD OF 2015 – 2018 - Lindawati, ASL; Hin, Jennifer (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine the effect of board diversity consisting of gender, tenure, and education diversity toward corporate social responsibility (CSR) disclosure. This research uses an external secondary data in the form of annual reports and also using sustainability reports of main sector companies listed in Indonesia Stock Exchange in 2015-2018. The selection of the sample uses purposive sampling method and in fact only obtained 8 companies per year, and for 4 years period with the total data sample are 32 samples. The data analysis uses multiple linear regression analysis use SPSS version 25. The partial results of this research show that gender and tenure variable have no significant effect on CSR disclosure, while education variable have a negative significant effect on CSR disclosure. However, board gender, tenure, and education diversity simultantly have effect on CSR disclosure.